Role of EU Grant Projects in Employment, Sectoral Employment and Innovation in Auto Repairing, Young Generations and New Horizons Project Case (European Journal of Marketing and Economics, 2023)
European Union Council Regulation (1085/2006 dated), the Financial Instrument for Pre-Accession (IPA) as well as for Turkey and potential candidate countries constitute the basis. The main objective of IPA is to assist the participating countries in dealing with European integration problems and undertaking the necessary reforms to comply with the Copenhagen criteria, which are EU membership requirements. Operation for Supporting Youth Employment in Sectoral Investment Areas (PYE-II) financed under IPA is carried out for employment, which is the primary target of its program. PYE-II operation, Turkısh Employment Agency(İŞKUR) has been implemented in Turkey by and the overall goal is to promote youth employment, retain more people in employment and increase the employment rate of young people. In this framework, the aim of supporting Youth Employment in Sectoral Investment Areas is to increase the employability of young people while promoting their integration into the labor market. Within the scope of the Grant Program for Supporting Youth Employment in Sectoral Investment Areas (PYE II), innovations were realized in the Auto Repair, Young Generations and New Horizons project. In this study; Innovations in the professional activities of the Auto Repair, Young Generations and New Horizons project, their contribution to employment in the automotive repair industry and their effects were announced.
Keywords: EU Grants, Project, Vehicle Care, Youth, Employment